Factors Associated with the Presence of Coliforms in the Feed and Water of Feedlot Cattle - Sanderson, Michael W.; Sargeant, Jan M.; Renter, David G.; Griffin, D. Dee; Smith, Robert A. (My University, 2005)
The objective of this study was to investigate coliform counts in feedlot cattle water and feed rations and their associations with management, climate, fecal material, and water Escherichia coli O157 using a cross-sectional study design. Coliform counts were performed on feed samples from 671 pens on 70 feedlots and on water samples from 702 pens on 72 feedlots in four U.S. states collected between May and August 2001. Management and climate factors were obtained by survey and observation. Month of sampling (higher in May and June), presence of corn silage in the ration (negative association), temperature of the feed 1 in. (ca. 2.5 cm) below the surface at the time of sampling (negative association), and wind velocity at the time of sampling (positive association) were significantly associated with log10 coliform levels in feed. Month of sampling (lower in May versus June July and August), water pH (negative association), and water total solids (positive association) were significantly associated with log10 water coliform levels. Coliform counts in feed and water were not associated with prevalence of E. coli O157 in cattle feces or water. Management risk factors must be interpreted with caution but the results reported here do not support the use of coliform counts as a marker for E. coli O157 contamination of feed or water.